Superovulatory response, embryo recovery and ovarian steroids in Jersey cows treated with different FSH preparations and their routes of administration - SARVAIYA, N P; PATEL, D M; PATHAK, M M; PATEL, A V; DUGWEKAR, Y G (The Indian Journal of Animal Reproduction, 2023)
A group of six regularly cycling Jersey cows were superovulated 18 times with (I) Folltropin-V 400 mg. NIH (Veterepharm, Inc. Canada) given in 8 equally divided intra muscular dose for 4 days, twice daily, (II) a single sub-cutaneous injection of Folltropin-V 400 mg. or (III) Super-ov 75 Units (Ausa Int.) in 8 divided descending intra muscular doses for 4 days. A luteolytic dose of PGFp (PG) was injected 60 latter. The cows exhibiting estrus after 36-48 hrs. were inseminated 2-3 times at 12 h. intervals. All the cows were flushed on day 7 post-breeding using DBPS (Sigma) and SOV (superovulatory) response and embryo yield recorded. Blood samples collected before, during and after treatment, were analysed for Progesterone (P4) and Estradiol-17p (E2) by standard RIA techniques. The results revealed that Folltropin and Super-ov treatment yielded 7.83±2.41 and 70 .. ±3.06 corpora lutea, (CL) and 12 and 9 transferable embroys, respectively, when administered intra muscularly in divided doses, whereas, single sub-cutaneous Folltropin V administration yielded 4.34 ±1.17 CI and 3 embryos, respectively. The serum E2 levels were high (85.03±36.94, 35.00±6.10 and 21.97±9.17 in groups I, II and III, respectively) on the day of SOV estrus. P4 levels elevated on the day of embryo recovery (5.57±1.39, 11.21±3.96 and 11.80±6.57), in groups I, II and III, respectively.